2015
DOI: 10.1177/230949901502300217
|View full text |Cite
|
Sign up to set email alerts
|

Local Infiltration Analgesia versus Standard Analgesia in Total Knee Arthroplasty

Abstract: Purpose.To compare outcome and cost following local infiltration analgesia (LIA) versus standard analgesia in total knee arthroplasty (TKA). Methods. 13 men and 33 women (mean age, 67.5 years) underwent TKA by a single surgeon and received LIA (n=24) or standard analgesia (n=22), depending on the availability of the senior anaesthetist. Results. The 2 groups were comparable at baseline in terms of age, gender, body mass index, American Society of Anesthesiologists score, and range of motion. Compared with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…4,26,27 We decide to compare FNB associating LIA because previous studies had well indicated the effectiveness of these two methods in relieving pain after knee replacement surgery. 18,20,22,35,37 Andersen and Kehlet 13,1428 and Xu et al 29 published recent reviews and studies about the effects of LIA in TKA. They concluded that LIA provides effective analgesia in the initial postoperative period after TKA in most randomized clinical trials even when combined with multimodal systemic analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…4,26,27 We decide to compare FNB associating LIA because previous studies had well indicated the effectiveness of these two methods in relieving pain after knee replacement surgery. 18,20,22,35,37 Andersen and Kehlet 13,1428 and Xu et al 29 published recent reviews and studies about the effects of LIA in TKA. They concluded that LIA provides effective analgesia in the initial postoperative period after TKA in most randomized clinical trials even when combined with multimodal systemic analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the article by Suthersan et al 1 We would like to discuss our experience: 1. Patients with severe varus/valgus deformity should be excluded, because of their increased analgesic requirement and thus delayed rehabilitation.…”
Section: To the Editormentioning
confidence: 99%
“…Local infiltration analgesia (LIA) has a short duration of analgesic action, which limits its clinical application. 7 A previous study reported that periarticular infiltration analgesia was effective and safe to reduce perioperative pain during the first 36 hours after TKA. 8 , 9 Its effects diminish with time, but this does not modify the postoperative course or the patient’s satisfaction at short-term follow-up.…”
Section: Introductionmentioning
confidence: 99%